COMBINED ORAL CONTRACEPTIVE PILLS IMPROVE LUNG FUNCTION VARIABLES - Shafiq, Mamoona; Sheikh, Sikandar Ali; Hassan, Syed Hafeezul (Pakistan Journal of Physiology, 2018)
Background: The combined oral contraceptive pill is an extremely effective method of contraception that also confers health benefits beyond pregnancy prevention. Oral contraceptive users have been found to have significantly higher total lung capacities when compared with nonusers. Methods: This study was carried out in Family Planning Centres at social obstetrical unit Baqai Medical University and Reproductive and Health Sciences (RHS) Institute, a family planning unit, at Jinnah Postgraduate Medical Centre Karachi, from November 2010 to April 2011. Fifty healthy non smoking women were given combined oral contraceptive pills containing Ethinyloestradiol 0.03 mg, Levonorgesterel 0.15 mg, ferrous fumerate 75.0 mg for six months. Results: At 6 months, Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), FEV1/FVC% and Peak Expiratory Flow Rate (PEFR) increased significantly. Conclusion: Combined oral contraceptives have a measurable effect on lung function variables.